13+3(2x-5)=1-2(3-6x)

Simple and best practice solution for 13+3(2x-5)=1-2(3-6x) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 13+3(2x-5)=1-2(3-6x) equation:


Simplifying
13 + 3(2x + -5) = 1 + -2(3 + -6x)

Reorder the terms:
13 + 3(-5 + 2x) = 1 + -2(3 + -6x)
13 + (-5 * 3 + 2x * 3) = 1 + -2(3 + -6x)
13 + (-15 + 6x) = 1 + -2(3 + -6x)

Combine like terms: 13 + -15 = -2
-2 + 6x = 1 + -2(3 + -6x)
-2 + 6x = 1 + (3 * -2 + -6x * -2)
-2 + 6x = 1 + (-6 + 12x)

Combine like terms: 1 + -6 = -5
-2 + 6x = -5 + 12x

Solving
-2 + 6x = -5 + 12x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-12x' to each side of the equation.
-2 + 6x + -12x = -5 + 12x + -12x

Combine like terms: 6x + -12x = -6x
-2 + -6x = -5 + 12x + -12x

Combine like terms: 12x + -12x = 0
-2 + -6x = -5 + 0
-2 + -6x = -5

Add '2' to each side of the equation.
-2 + 2 + -6x = -5 + 2

Combine like terms: -2 + 2 = 0
0 + -6x = -5 + 2
-6x = -5 + 2

Combine like terms: -5 + 2 = -3
-6x = -3

Divide each side by '-6'.
x = 0.5

Simplifying
x = 0.5

See similar equations:

| 3c-1c+40=34 | | 4/3+2=6 | | x+2x+13=70 | | 7.5-(-2.5)= | | a(c-2)+3(c-2)= | | 92=-8+25m | | x+.05x=23.63 | | -(5+2x)=2(3+4x) | | 5t-14=8t+4 | | 3(n-5)=9-n | | 2x+4=-1(7x+6) | | 1(5+2x)=2(3+4x) | | 8y-8=64 | | 5y/6-23=7 | | 350x23/20x7/25 | | 5t-1=24 | | 3.0-(-5.3)= | | 5+X+X=1+4X | | x+.06x=22.64 | | 4x+6+x=3+2x-3 | | x+4(x+1)=47 | | 2t-5=29 | | 2(3n-4)=-26+3n | | 2x+61=3x-8 | | -11=4u+5 | | 5y-16=49 | | 3+1.5(z+2)=3.5z-2 | | 3+7d=-4 | | -5r+36=-7(8+4r) | | 3(c-6)=10+2c | | 0.03(2c-50)=-0.6(c-3) | | f(0.5)=-4(x)+3 |

Equations solver categories